Ketamine administration in idiopathic epileptic and healthy control dogs: Can we detect differences in brain metabolite response with spectroscopy? - Wieser, Manuela; Beckmann, Katrin Melanie; Kutter, Annette P. N.; Mauri, Nico; Richter, Henning; Zölch, Niklaus; Bektas, Rima Nadine (Frontiers in Veterinary Science, 2023)
In recent years ketamine has increasingly become the focus of multimodal emergency therapy for epileptic seizure. However, little is known about the effect of ketamine on brain metabolites in epileptic patients. Magnetic resonance spectroscopy is a non-invasive technique to estimate brain metabolites in vivo. Our aim was to measure the effect of ketamine on thalamic metabolites in idiopathic epileptic (IE) dogs using 3 Tesla magnetic resonance spectroscopy. We hypothesized that ketamine would increase the Glutamine – Glutamate (Glx)/Creatine ratio in epileptic dogs with and without antiepileptic drug treatment, but not in control dogs. In this controlled prospective experimental trial IE dogs with or without antiepileptic drug treatment and healthy relative client-owned Border Collies and Greater Swiss Mountain Dogs were included. After sedation with butorphanol, induction with propofol and maintenance with sevoflurane in oxygen and air, a single voxel magnetic resonance spectroscopy at the level of the thalamus was performed before and 2 minutes after intravenous administration of 1 mg/kg ketamine. An automated data processing spectral fitting linear combination model algorithm was used to estimate metabolite ratios. A mixed ANOVA with the independent factor within subjects’ ketamine administration and between subjects group allocation was performed for all measured metabolites. A p < 0.05 was considered statistically significant. Twelve healthy control dogs, 10 untreated IE and 12 treated IE dogs were included. No significant effects of ketamine administration (p = 0.356), group allocation (p = 0.073) and interaction (p = 0.4) for Glx/Creatine were found. However, increased Glucose/Creatine ratios were found (p < 0.001) with no effect of group allocation. Furthermore, a significant interaction between group allocation and ketamine administration (p = 0.038) for GABA/Creatine was detected. MRS was able to detect changes in metabolite/Creatine ratios after administration of 1 mg/kg intravenous ketamine in dogs, but only a difference in the response was detected between IE and healthy control dogs for GABA/Creatine ratio but not for Glx/Creatine ratio.